Relationship between High School Students' Facebook Addiction and Loneliness Status - Karakose, Turgut; Yirci, Ramazan; Uygun, Harun; Ozdemir, Tuncay Yavuz (Modestum Ltd, 2016)
This study was conducted in order to analyze the relation between high school students' Facebook addiction and loneliness levels. The study was conducted with the relational screening model. The sample of the study consists of 712 randomly selected high school students. The data was collected using the Bergen Facebook Addiction Scale (BFAS) to analyze the students' Facebook tendencies and with the UCLA Loneliness Scale to analyze the students' levels of loneliness. Data was analyzed with descriptive statistic instruments along with t-test, ANOVA test, LSD test, and Correlation Analysis. Research findings suggest that the Facebook addiction levels of the high school students in the sample are rather low. Analyses conducted regarding the gender variable indicate that there is no relationship between Facebook addiction levels and the time spent on Facebook. Findings show that students most commonly share photographs and videos. This suggests that students use Facebook as a leisure pastime. Also, analyses indicate that there is a statistical significant relationship between the time participants spend on Facebook and their Facebook addiction scores. Findings of the study suggest that both male and female students' loneliness scores are low. In addition, the Correlation Analysis conducted to determine participants' Facebook addiction and loneliness levels was examined and no statistical significant relationships were found. According to the findings, it can be asserted that the participants of this study are not in the risk group regarding their Facebook addiction and loneliness levels.
Keywords: facebook addiction; loneliness; internet; high school students; social media